KEBIJAKAN SOSIAL DAN OTONOMI DAERAH - Baharuddin Thahir (Fakultas Politik Pemerintahan IPDN, 2019)
Social Policy and Regional Autonomy. The policy of decentralization and the practice of regional autonomy in Indonesia is a tool in the realization of the ideals of justice, democracy and the welfare of the people. This study aims to discuss social policy and regional autonomy in accordance with the author’s understanding of the various sources obtained. This study uses a qualitative approach with descriptive methods. Data collection techniques in this study, the authors use literature review. In other words all efforts made by the author to gather information that is relevant to the topic or problem being discussed. The results show that the practice of governance today shows that social policy has been carried out. The national government and the regional government make social policy a matter that must be done in implementing government affairs. In decentralization, social policy has its own place in implementing government affairs. In that context social policy is understood as a policy and program run by the government, which is designed to improve people’s welfare or increase human dignity. Keywords: social policy, local government, regional autonomy.